Associations of distraction involvement and age with driver injury severities. (February 2015) - Donmez, Birsen; Liu, Zishu
Abstract: Introduction: This paper investigates the associations between the severity of injuries sustained by a driver who is involved in a two-vehicle crash, the existence and type of driver distraction as well as driver's age. Few studies investigated distraction as it relates to injury severity. Moreover, these studies did not consider driver age which is a significant factor related to driving behavior and the ability to respond in a crash situation. Methods: An ordered logit model was built to predict injury severity sustained by drivers using data from the U.S. National Automotive Sampling System's General Estimates System (2003 to 2008). Various factors (e.g., weather, gender, and speeding) were statistically controlled for, but the main focus was on the interaction of driver age and distraction type. Results: The trends observed for young and mid-age drivers were similar. For these age groups, dialing or texting on the cell phone, passengers, and in-vehicle sources resulted in an increase in a likelihood of more severe injuries. Talking on the cell phone had a similar effect for younger drivers but was not significant for mid-age drivers. Inattention and distractions outside the vehicle decreased the odds of severe injuries. For older drivers, the highest odds of severe injuries were observed with dialing or texting on a cell phone, followed by in-vehicle sources and talking on the cell phone. All these sources were associated with an increased likelihood of injury severity. Similar to young and mid-age drivers, distractions outside the vehicle decreased the odds of severe injuries. Other distraction types did not have a significant effect for the older age group. Conclusions: The results support previous literature and extend our understanding of crash injury severity. Practical applications: The findings have implications for policy making and the design of distraction mitigation systems. Highlights: We modeled the likelihood of driver injury severities given distraction type and age Likelihood reduced with inattention and distractions outside the vehicle Likelihood increased with cell phone, passengers, and in-vehicle sources Talking on cell phone was not significant for mid-age drivers Inattention and passenger distractions were not significant for older drivers